An image reconstruction method for endoscopic photoacoustic tomography in tissues with heterogeneous sound speed. (July 2019) - Zheng, Sun; Yixuan, Jia
Abstract: The idealized assumption of a constant speed of sound (SOS) in acoustically inhomogeneous biological tissues usually results in blurred details, acoustic distortion and artifacts in in vivo endoscopic photoacoustic tomographic (EPAT) images. In this paper, we propose an image reconstruction method to improve EPAT imaging for luminal structures with the variable SOS. In our method, an optimal SOS providing the maximal local focusing of a measuring location within the imaging region is firstly determined. The deviation in the ultrasonic propagation time caused by the variable SOS is then compensated. The grayscale images of the optical absorption distribution on the cross-sections of the luminal structures are finally reconstructed with a filtered back-projection (FBP) algorithm based on the corrected propagation time. Any prior knowledge of the SOS distribution in the imaged tissues is not required. The results of numerical simulation experiments demonstrated that the proposed method can effectively improve the image quality by reducing the misalignment of tissues, acoustic distortion and artifacts caused by the variable SOS.